2008
DOI: 10.1073/pnas.0802302105
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C epsilon mediation of CRF- and ethanol-induced GABA release in central amygdala

Abstract: In the central amygdala (CeA), ethanol acts via corticotrophinreleasing factor (CRF) type 1 receptors to enhance GABA release. Amygdala CRF mediates anxiety associated with stress and drug dependence, and it regulates ethanol intake. Because mutant mice that lack PKC exhibit reduced anxiety-like behavior and alcohol consumption, we investigated whether PKC lies downstream of CRF1 receptors in the CeA. Compared with PKC ؉/؉ CeA neurons, PKC ؊/؊ neurons showed increased GABAergic tone due to enhanced GABA releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(148 citation statements)
references
References 42 publications
10
136
2
Order By: Relevance
“…Given the recent evidence that central ghrelin signaling influences alcohol intake (Jerlhag et al, 2009;Kaur and Ryabinin, 2010), we sought to determine whether activation of CeA GHS-R1As by ghrelin would alter the effects of ethanol on GABAergic transmission. To test the influence of GHS-R1A activation on ethanol-induced augmentation of IPSPs, we first superfused a maximal concentration of ghrelin (100-200 nM) onto CeA slices and then added 44 mM ethanol (a dose producing maximal effects; Roberto et al, 2003;Bajo et al, 2008) in the continued presence of ghrelin. We pooled the data from different doses of ghrelin because our dose-response experiments demonstrated that there was no change in the magnitude of effect at these different concentrations (Figure 1c).…”
Section: Acute Ethanol Interacts With Ghrelin Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the recent evidence that central ghrelin signaling influences alcohol intake (Jerlhag et al, 2009;Kaur and Ryabinin, 2010), we sought to determine whether activation of CeA GHS-R1As by ghrelin would alter the effects of ethanol on GABAergic transmission. To test the influence of GHS-R1A activation on ethanol-induced augmentation of IPSPs, we first superfused a maximal concentration of ghrelin (100-200 nM) onto CeA slices and then added 44 mM ethanol (a dose producing maximal effects; Roberto et al, 2003;Bajo et al, 2008) in the continued presence of ghrelin. We pooled the data from different doses of ghrelin because our dose-response experiments demonstrated that there was no change in the magnitude of effect at these different concentrations (Figure 1c).…”
Section: Acute Ethanol Interacts With Ghrelin Effectsmentioning
confidence: 99%
“…Microinjection of GABA A receptor antagonists into the CeA blocks the reinforcing effect of alcohol (Hyytia and Koob, 1995), and injection of GABA A receptor agonists and benzodiazepines into the CeA decreases anxiety (Roberts et al, 1996), supporting the involvement of the CeA GABAergic system in ethanol reinforcement. We have previously reported that ethanol augments GABAergic transmission in CeA neurons via a presynaptic mechanism that enhances GABA release (Roberto et al, 2003(Roberto et al, , 2010Nie et al, 2004;Bajo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Potentiation of GABA release onto cerebellar Purkinje neurons is eliminated in the presence of AC and protein kinase A (PKA) inhibitors (Kelm et al 2008), and is also affected by compounds targeting phospholipase C and PKC (Kelm et al 2010). The potentiating effect of EtOH is impaired in central amygdala (CeA) in mice that lack PKCε (Bajo et al 2008). Thus, PKC is implicated in both the pre and postsynaptic effects of EtOH at GABAergic synapses.…”
Section: Presynaptic Effects Of Ethanolmentioning
confidence: 99%
“…Acute EtOH augments evoked GABA A receptor-mediated inhibitory postsynaptic currents (IPSCs) by increasing GABA release in both mouse (Bajo et al 2008;Nie et al 2004) and rat CeA neurons (Roberto et al 2003(Roberto et al , 2004.…”
Section: Corticotropin-releasing Factormentioning
confidence: 99%
See 1 more Smart Citation